2002
DOI: 10.1097/00001756-200212200-00016
|View full text |Cite
|
Sign up to set email alerts
|

Orbitofrontal cortex dysfunction in attention-deficit hyperactivity disorder revealed by reversal and extinction tasks

Abstract: Attention-deficit hyperactivity disorder (ADHD) has been considered a mental illness in which the frontal lobe is dysfunctional. The orbitofrontal cortex (OFC) controls emotional and motivational behaviors which are impaired in ADHD. Patients with OFC damage have shown impaired performance in reversal and extinction tasks in a simple go/no-go paradigm. We assigned ADHD subjects the two tasks to examine a hypothesized dysfunction of OFC. ADHD subjects indeed showed a performance deficit in the tasks, supporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 23 publications
1
64
2
Order By: Relevance
“…Neuropsychological analyses have shown that patients with ADHD are impaired on the same tasks as those with prefrontal lesions, for example, tasks of behavioral inhibition, reward reversal, and working memory (Itami and Uno, 2002;Bedard et al, 2003;McLean et al, 2004). Although some neuropsychological studies disagree with the importance of executive function deficits in ADHD, these studies are often flawed by the use of inappropriate tasks for evaluating children (eg the Stroop color-naming interference task, which assumes that reading is a prepotent response that must be inhibited, an assumption often invalid in children; van Mourik et al, 2005), disagreement on which processes constitute executive functions (eg not including attention regulation parameters as executive functions; Schoechlin and Engel, 2005), or by the use of tasks with ceiling effects for this patient population.…”
Section: Prefrontal Cortical Dysfunction In Adhdmentioning
confidence: 99%
“…Neuropsychological analyses have shown that patients with ADHD are impaired on the same tasks as those with prefrontal lesions, for example, tasks of behavioral inhibition, reward reversal, and working memory (Itami and Uno, 2002;Bedard et al, 2003;McLean et al, 2004). Although some neuropsychological studies disagree with the importance of executive function deficits in ADHD, these studies are often flawed by the use of inappropriate tasks for evaluating children (eg the Stroop color-naming interference task, which assumes that reading is a prepotent response that must be inhibited, an assumption often invalid in children; van Mourik et al, 2005), disagreement on which processes constitute executive functions (eg not including attention regulation parameters as executive functions; Schoechlin and Engel, 2005), or by the use of tasks with ceiling effects for this patient population.…”
Section: Prefrontal Cortical Dysfunction In Adhdmentioning
confidence: 99%
“…The ability to shift 'set' or response is suboptimal in a number of psychiatric disorders, namely schizophrenia, drug addiction, and attention deficit/hyperactivity disorder (Crider, 1997;Itami and Uno, 2002;Fillmore and Rush, 2006). Indeed, we have previously emphasized the face validity for impairments in the ability to stop or change ongoing responses for key psychopathological aspects of drug dependence and abuse (Jentsch and Taylor, 1999).…”
Section: Implications For Mental Disordersmentioning
confidence: 99%
“…With regard to a possible involvement of 5-HT 2C receptors in ADHD, two studies report changes in the allelic distribution of two polymorphisms in the promoter region of the 5-HT 2C receptor gene in ADHD populations (Li et al, 2006;Xu et al, 2009), although not all studies have revealed an association (Bobb et al, 2005;Brookes et al, 2006). Although mutations resulting in the complete absence of 5-HT 2C receptor expression have not been reported in humans, the potential relevance of 2CKO mice to ADHD is further suggested by the expression of several behavioral phenotypes relevant to this syndrome, including attentional impairment, reduced behavioral flexibility, physical hyperactivity, and obesity (Tecott et al, 1995;Itami and Uno, 2002;Nonogaki et al, 2003;Dempsey et al, 2011;Cortese and Vincenzi, 2012). Thus, it is possible that insights into how a more robust genetic perturbation (knockout) of 5-HT 2C receptor function impacts executive function may facilitate attempts to understand the neural mechanisms through which common more subtle genetic alterations of 5-HT 2C receptor function impact disease pathophysiology.…”
Section: Discussionmentioning
confidence: 99%